Jurnal ILMU KOMUNIKASI: MAGDALENE.CO SEBAGAI MEDIA ADVOKASI PEREMPUAN - Eni Maryani, Justito Adiprasetio (PRODI Ilmu Komunikasi UAJY, 2017)
The subordination of women intertwined with patriarchy culture in the society. Magdalene.co is one of online media to advocate women. The study tries to reveal Magdalane.co’s creative efforts in undertaking gender-sensitive journalism and advocacy journalism for women. Content analysis, interviews, and literature studies are conducted for collecting data